Characteristics of graft‐versus‐host disease occurring after alemtuzumab‐containing allogeneic stem cell transplants: incidence, organ involvement, risk factors and survival. (12th November 2019) - Finazzi, Maria C.; Boschini, Cristina; Craddock, Charles; Rambaldi, Alessandro; Ward, Janice; Malladi, Ram K.
Summary: T‐cell depletion with alemtuzumab represents an effective form of graft‐ versus ‐host disease (GVHD) prophylaxis after allogeneic haematopoietic stem cell transplantation (allo‐HSCT); however, little is known regarding the impact of in vivo alemtuzumab on either the incidence or clinical characteristics of acute and chronic GVHD. We therefore studied 201 consecutive adult patients who received an alemtuzumab‐based, reduced‐intensity conditioned (RIC) allograft. With a median follow‐up of 24 months, the cumulative incidence of classic acute and late acute (persistent, recurrent and late onset) GVHD grades II–IV (grades III–IV) was 34% (13%) and 20% (8%) respectively; the cumulative incidence of classic chronic GVHD and overlap syndrome were 4% and 7% respectively. A previous diagnosis of classic acute GVHD is a risk factor for chronic GVHD (hazard ratio 10·91, 95% confidence interval 2·35–50·63, P = 0·0023) while late onset acute GVHD is not a risk factor for later development of chronic GVHD. Unrelated donor transplant is a risk factor for the development of classic acute GVHD but not for late onset or chronic GVHD. In conclusion, this study describes a distinctive pattern of GVHD following alemtuzumab‐RIC allografts, identifies the risk factors for GVHD development and provides prognostic information of patients with GVHD.